Spontaneous miscarriages and infant deaths among female farmers in rural South Africa - Saloshni Naidoo; Leslie London; Alex Burdorf; Rajen Naidoo; Hans Kromhout (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVES: This study examined associations of demographics and occupational factors with spontaneous miscarriages and infant deaths among women working in agriculture in KwaZulu-Natal, South Africa. METHOD: This cross-sectional study in 2006 described and compared reproductive outcomes among 911 women working in agriculture in two distinct areas (ie, the irrigation scheme and drylands) of the Makhatini Flats, KwaZulu-Natal, South Africa. Associations between demographics, agricultural activities, physical load, pesticide spraying and self-reported "spontaneous miscarriage" and "infant death" (death in the first year) were explored using univariate and multivariate analyses. Results Women (N=887) reported 4796 pregnancies, 322 spontaneous miscarriages, 137 infant deaths. Adjusting for age, education, and length of recall of pregnancy, spraying pesticides during the first three months of a pregnancy was associated with spontaneous miscarriage [irrigation scheme odds ratio (OR) 2.8, (95% CI) 1.1-7.2; drylands OR 2.5, 95% CI 1.2-5.6]. Irrigation scheme women aged ≥40 years were more likely to report spontaneous miscarriage (OR 3.1, 95% CI 1.2-8.2). Owning one's farm or working a family farm among irrigation scheme women (OR: 2.3; 95 % CI 1.2-4.4) and working for ≥10 years among drylands women (OR 2.1, 95 % CI 1.1-4.3) were associated with infant death. Weeding was inversely associated with infant death among irrigation scheme women (OR 0.4, 95 % CI 0.2-0.7). CONCLUSION: This study found that women reporting spontaneous miscarriage were more likely to have sprayed pesticides during pregnancy, and those reporting infant death were more likely to have owned their farms and worked longer in agriculture.